EFFICACY OF PHYSICAL TRAININGS AS CARDIOPROTECTION METHOD FOR CORONARY BYPASS SURGERY - Yu. A. Argunova; A. A. Korotkevich; S. A. Pomeshkina; A. N. Kokov; A. A. Inozemtseva; О. L. Barbarash (Российский кардиологический журнал)
Aim. To assess efficacy and safety of inclusion of physical trainings to the program of patients prehabilitation before coronary bypass (CBG) on-pump, from the perspective of cardioprotection.Material and methods. Totally, 38 patients included, randomized to 2 group depending on prehabilitation program. Group 1 patients (n=20, mean age 57,9±7,2 y. o.) at the stage of prehabilitation, underwent serial physical trainings of high intensity; in group 2 (n=18, mean age 60,4±7,01 y. o.) there were none. Evaluation of the target parameters of myocardial perfusion was done before the training and in post-operation period with single photon emission tomography (SPECT).Results. In the group with included exercises, during post-surgery period there was significantly higher level of radiopharmacological marker capture comparing to nontrained group in some basal segments (74,9±3,98% and 70,3±7,40%, respectively, р=0,04), middle (86,7±5,24% and 79,6±10,43%, resp., р=0,03) and apical (85,8±5,03% and 79,0±8,67%, resp., р=0,02) portions of myocardium, by SPECT. Integral value of the stress-induced temporary ischemia (SDS) after CBG in training group was significantly lower than in non-training group (0 and 0,9±0,53 pts., resp., р=0,04). Dynamics analysis of the parameters of myocardial perfusion demonstrated significant decrease of the parameter characterizing perfusion defect with adenosin load (SSS) (р=0,013), and SDS (р=0,018) in the group of exercises after operation comparing to pre-operational values. In non-training group the dynamics was nonsignificant.Conclusion. According to the data obtained, inclusion of physical trainings of high intensity to the program of prehabilitation of patients before CBG leads to improvement of myocardial perfusion parameters in post-operation period, that possibly optimizes the outcomes of surgery.